Candidate Selection, Personalization and Different Logics of Centralization in New Southern European Populism: The Cases of Podemos and the M5S - Caiani, Manuela; Padoan, Enrico; Marino, Bruno (Government and opposition (London), 2022)
In this article, we focus on the candidate selection processes of Podemos in Spain and the Movimento 5 Stelle (M5S – Five Star Movement) in Italy, processes which are related to intra-party democracy. With a mixed-methods approach (including novel data from the expert survey PoPES, 31 semi-structured interviews with party representatives and militants, and analysis of party documents, statutes and leader speeches) and a comparative perspective, we explore candidate selection in the context of the broader organizational party structures over time. We find that: (1) Podemos functions like a typical centralized party, whereas M5S is a deviant case with strong and centralized control over party organization but decentralized mechanisms for candidate selection; (2) both these logics of centralization of power undermine the parties’ democratic credentials but have different consequences in terms of cohesion (expulsions/departures in M5S and splintering in Podemos); and (3) in both cases, the parties’ organizational culture and symbolic tools legitimate their top-down features.